An investigation of the associations between stigma, self-compassion, and pain outcomes during treatment based on Acceptance and Commitment Therapy for chronic pain - Anderson, Madeleine; McCracken, Lance M.; Scott, Whitney (Frontiers in Psychology, 2024)
Introduction: Stigma adversely affects people with chronic pain. The qualities within selfcompassion may be particularly useful for buffering the impact of stigma on people with pain. In the context of an Acceptance and Commitment Therapy-based (ACT) treatment for chronic pain, this study investigated the association between changes in stigma and selfcompassion and pain outcomes, and the potential moderating role of self-compassion on the association between stigma and pain outcomes. Materials and Methods: Five-hundred and nineteen patients completed standardized self-report questionnaires of stigma, selfcompassion, psychological flexibility, pain intensity and interference, work and social adjustment, and depression symptoms at the start of an interdisciplinary ACT-based treatment for chronic pain. The same measures were completed at post-treatment (n=431). Results: The results indicated that key pain outcomes and self-compassion significantly improved during treatment, but stigma did not. Changes in stigma and self-compassion were significantly negatively correlated and changes in these variables were associated with improvements in treatment outcomes. There were significant main effects of stigma and self-compassion for many of the pre-and post-treatment regression models when psychological flexibility was not controlled for, but self-compassion did not moderate the association between stigma and pain outcomes. Stigma remained significant when psychological flexibility variables were controlled for, while self-compassion did not. Discussion: The findings add to our conceptual understanding of the inter-relationships between stigma, self-compassion, and psychological flexibility and can contribute to treatment advancements to optimally target these variables.